Morinda citrifolia (noni) na alimentação de ovinos - Veloso, Luiz Eduardo Cantão (2016)
This study aimed to evaluate the inclusion of 0.0%; 0.7%; 1.4% and 2.1% of noni in sheep feeding confined on consumption and total tract digestibility of nutrients, ruminal parameters, feeding behavior and physiological variables of sheep in confinement. an experimental design in a double Latin square (4X4) with eight animals was used (lambs), four periods and four experimental diets with different levels of Noni in sheep feeding. 8 lambs were mongrel with body weight (BW) Average Initial 23.74 ± 1 kg. The concentrate roughage was 65:35. The experiment lasted 84 days, divided into four periods lasting 21 days, 14 days for animal adaptation and 7 days of collection. During the collection period (seven days), there were total feces collection, supplied food, leftovers and the last day of each collection period was conducted sampling of ruminal fluid (0h before the food supply, 2, 4 , 6 and 8 hours after the delivery of food). The feeding behavior of the animals were carried out on the last day of each experimental period. The physiological and environmental variables were measured for three days of each period. consumption variables and nutrient digestibility and ruminal parameters were interpreted by analysis of variance, and the feeding behavior data and physiological variables was preceded subdivision of the plot, considering the day and night time evaluation for feeding behavior and morning and afternoon to the physiological variables, which were submitted to regression in the program Statistical Analysis System and Genetics - SAEG. The different levels of inclusion of 0.0%, 0.7%, 1.4% and 2.1% of Noni in lambs diets did not affect (p> 0.05) consumption of dry matter (DM); organic matter (OM); crude protein (CP); neutral detergent fiber (NDF); acid detergent fiber (FDA); total carbohydrates (CHT) and non-fiber carbohydrates (NFC) expressed in grams pet day (g Animal-1 day-1); percentage of body weight (BW) and grams per kilogram of metabolic body weight (g kg0.75 -1). However, for the consumption of ether extract (EE), presented quadratic behavior (p <0.05) with the inclusion of noni in feed. The inclusion of Noni in the experimental diets provided no change (p> 0.05) in total tract digestibility coefficients (DC) of MS; MO; PB; AND FDN. Similarly the inclusion of the Noni, did not change the values of pH and concentration of ammonia nitrogen (NH3-N) of rumen fluid. However, the pH and the concentration of NH3 in the ruminal fluid differed (P <0.05) versus time (t) for all the experimental diets. The different levels of addition of Noni (0,0% 0 , 7%, 1.4% and 2.1%) for the feeding of lambs did not change (p> 0.05) the time values used in minutes for ingestive behaviors to consumption activity of dry matter (DM) rumination (RUM), leisure (OCI) and water consumption (CAG). However, the inclusion of different levels of Noni (0.0%, 0.7%, 1.4% and 2.1%) in the diet of sheep changed (p <0.05) cubic way the time in minutes used for other activities (OAT), the average regression equation to explain OAT value was Y = 123,2100+ 20,1250X - 2,5255X2 for all experimental diets. The day and night periods changed (p <0.05) the time used for CMS activities; RUM; CAG expressed in minutes. For RUM activity, the time used was higher (p> 0.05) for the night period for daytime. The OCI activity, there was no interaction between the diets with the inclusion of 0.0%; 0.7% and 2.1% of Noni; in different periods (day and night) analyzed; the time spent in this activity was higher (p <0.05) at night. However, there was interaction between the periods within the 1.4% feed. The CAG activity xiii had higher performance (p> 0.05) during the day. For OAT, during the day showed a quadratic effect between the experimental diets, unlike the night shift, which which showed linear effect (p <0.05). The inclusion of different levels of Noni did not change (p> 0.05) analyzed the physiological variables (rectal temperature, temperature of the anterior and posterior limbs and respiratory rate) in different periods (morning and afternoon), however, the values were higher the period late. Thus, it is concluded that the level of up to 2.1% inclusion of noni in feeding lambs does not alter the consumption and the coefficient of total tract digestibility of nutrients, ruminal parameters, feeding behavior and physiological variables, however the day and night periods and morning and afternoon, influence variable values for feeding behavior and physiological variables.